PELAKSANAAN KOORDINASI PENERTIBAN USAHA PENGELOLAAN DAN PENGUSAHAAN SARANG BURUNG WALET DI KOTA PEKANBARU - Chandra, Rizki; Sahuri, Chalid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Rizky Chandra 0801134161, Managemnet adn Exploitation Permit Swallow Nest Pekanbaru.Implementation Coordination In Business Control Management and Operation Swallow's Nest PekanbaruIssuance of the Regional Regulation No. 3 of 2007 on Business License Management and Operation Swallow's Nest in the city of Pekanbaru in the underlying by his many swiftlet entrepreneurs in the city of Pekanbaru. Swiftlet entrepreneurs is growing and growing every year so it starts to cause discomfort in the center of the community. The purpose of the issuance of this rule is more discipline swiftlet entrepreneurs as opposed to the regional regulation of Pekanbaru. To overcome this problem swallow , the government on education through the coordinating efforts of management and operations control of bird's nest in the city of Pekanbaru. The formation of the team by virtue of a decision of the Head of Department of Agriculture : Distan/523.3/679/IX/2012. The team is composed of law enforcement Dina Pekanbaru Agriculture , Department of Spatial Planning and Building Pekanbaru , Pekanbaru City Environment Agency and Civil Service Police Unit of Pekanbaru. Based on such matters with the researcher wishes to conduct a descriptive study on the implementation of Law Enforcement Coordination in Business Management and Operation Swallow's Nest in the city of Pekanbaru and the factors that affect the implementation of coordination in business management and operation control of bird's nest in the city of Pekanbaru.The concept of the theory is that researchers use coordination theory according to Henry Fayol , Harold Koonzt , and Cyriil O'donel , the indicators in this study are communication , cooperation , division of tasks and meetings through conference. The author combines the author of several major theories on theoretical concepts. While the factors which influence based on research found in the field. Researchers used interviews and observation techniques using Key informant as a resource of information and through snowball sampling method obtained subsequent informants.The results of the study , it can be concluded that the implementation of coordination in business management and operation control of bird's nest in the city of Pekanbaru is not running at max. The factors that affect the implementation of coordination in the enforcement of business management and operation srang swiftlet in Pekanbaru ie, matching time and budget. Both of these factors affect theimplementation of coordination in business management and operation control of bird's nest in the city of Pekanbaru.Keywords: Coordination, communication, cooperation, division of labor, through meetings of meetings